Prognostic value of systemic immune-Inflammatory index in patients with diabetes mellitus and acute coronary syndrome after percutaneous coronary intervention: a prospective cohort study - Leli Zhang; Shen Wang; Yue Wang; Pengrong Guo; Shou Pang; Boqun Shi; Xiaofan Wu (BMC Cardiovascular Disorders)
Abstract Background A higher risk of cardiovascular disease has been correlated with several inflammatory biomarkers, one of which is the systemic immune-inflammatory index (SII). Nevertheless, the relationship between SII and major adverse cardiovascular and cerebrovascular events (MACCE) in patients with diabetes and acute coronary syndrome (ACS) after percutaneous coronary intervention (PCI) remains unclear. The objective of this study was to assess the prognostic value of SII for the risk of MACCE in patients with diabetes and ACS who underwent PCI. Methods This study included 1782 patients with ACS and diabetes who underwent PCI successfully at Beijing Anzhen Hospital between August 2021 and April 2022, with a median follow-up of 16.2 months. According to the optimal SII cut-off value for MACCE, patients were categorized into two groups: the high SII group (SII ≥ 735.82 × 109/L, n = 576) and the low SII group (SII < 735.82 × 109/L, n = 1206). Univariate and multivariate Cox regression were used to verify the relationship between SII and MACCE, and the reliability of the relationship was further tested by subgroup analysis. Results The incidence of MACCE was significantly higher in the high SII group than in the low SII group (11.3% vs. 6.7%, log-rank P < 0.001), indicating that among 22 patients with high SII levels, an additional MACCE event is expected to occur. Univariate Cox proportional hazards models showed that higher SII was associated with an increased incidence of MACCE (HR: 1.739, 95%CI: 1.254–2.410). After full adjustment, higher SII remained an independent risk factor for MACCE (HR: 1.540, 95%CI: 1.098–2.160) and unplanned revascularization (HR: 1.526, 95%CI: 1.011–2.301). Conclusion This study found that elevated SII is an independent risk factor for predicting MACCE in patients with ACS and diabetes mellitus after PCI, providing a theoretical basis for postoperative anti-inflammatory therapy in this population.